Breeding for resistances to Ralstonia solanacearum - Huet, Gaëlle (Frontiers in Plant Science, 2014)
Ralstonia solanacearum is one of the most devastating bacterial plant pathogens due to its large host range, worldwide geographic distribution and persistence in fields. This soilborne pathogen is the causal agent of bacterial wilt and it can infect major agricultural crops thereby reducing significantly their yield. To favour infection, the bacterium delivers, through the type three secretion system, effectors that manipulate plant immunity. In this review, the relative efficiency of control strategies and existing resistances to R. solanacearum will be presented. Then, we will describe the genetic and molecular insights gained from the study of bacterial wilt in model plants. Finally, we will explore how the knowledge gathered from unravelling avirulence and virulence mechanisms of R. solanacearum effectors could help to develop more durable resistances in crop plants toward this destructive pathogen.